2018
DOI: 10.12669/pjms.344.14760
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression among adults with sickle cell disease in the Southern Region of Saudi Arabia

Abstract: Objectives:Sickle Cell Disease (SCD) as other chronic medical conditions is commonly complicated by psychiatric symptoms. Saudi SCD patients are usually originally from Eastern and Southwestern Provinces. The main objective of our study was to evaluate the prevalence of depression among adults with SCD in southern region of Saudi Arabia. We also studied the sociodemographic profiles for these individuals.Methods:We conducted a cross-sectional study among subjects (n=78) in Armed Forces Hospital, Southern Saudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 16 publications
3
25
0
Order By: Relevance
“…Although some studies have evaluated the association between SCD and comorbid depression, there is a dearth of literature relating to gender differences among adult SCD patients with comorbid depression. There are a few studies which show no significant association between gender and comorbid depression among SCD patients [25,26,27]. However, our results are consistent with findings from other studies, which also reported that comorbid depression was significantly higher among females with SCD compared to males [12,14,28].…”
Section: Discussionsupporting
confidence: 91%
“…Although some studies have evaluated the association between SCD and comorbid depression, there is a dearth of literature relating to gender differences among adult SCD patients with comorbid depression. There are a few studies which show no significant association between gender and comorbid depression among SCD patients [25,26,27]. However, our results are consistent with findings from other studies, which also reported that comorbid depression was significantly higher among females with SCD compared to males [12,14,28].…”
Section: Discussionsupporting
confidence: 91%
“…When compared to other chronic conditions, the depression prevalence among keratoconus patients in Saudi Arabia is at the middle ground between higher depression rates of sickle cell anemia (48.2%-85.9%) [ 22 , 23 ] and chronic pain (71%) [ 24 ] and lower depression rates of chronic kidney disease (6.8%-24.6%) [ 25 , 26 ] and type 2 diabetes mellitus (33.8%) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…(20) One study with 78 participants, in southern Saudi Arabia, identified a larger proportion of women (64.1%) with SCD. (21) In another observational study conducted in the state of Wisconsin, the number of women receiving care in the outpatient clinic was 64 (65%). (22) Also in the United States, in another study conducted by the University of Illinois, 86 (65%) were women.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 200 participants with HbSS (1 -49 years old) attending the hematology clinics of Lagos University Hospital, Nigeria, revealed that the mean age was 18.8 ± 14.39 years; in another, developed in southern Saudi Arabia, with a group of 78 receiving care at a referral hospital, the mean was 26.4 ± 9.2 years. (21) The advent of neonatal screening, antibiotic prophylaxis, better vaccines, safer blood transfusion, iron chelation, and hydroxyurea therapy have improved the survival of patients with SCD. (17,(23)(24)(25)(26)(27) The life expectancy of children has increased, and SCD changed from a childhood disease to become a chronic disease.…”
Section: Discussionmentioning
confidence: 99%